2014
DOI: 10.1128/mbio.00070-14
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Viruses and mRNA Splicing: Doing More with Less

Abstract: During their nuclear replication stage, influenza viruses hijack the host splicing machinery to process some of their RNA segments, the M and NS segments. In this review, we provide an overview of the current knowledge gathered on this interplay between influenza viruses and the cellular spliceosome, with a particular focus on influenza A viruses (IAV). These viruses have developed accurate regulation mechanisms to reassign the host spliceosome to alter host cellular expression and enable an optimal expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
134
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(136 citation statements)
references
References 105 publications
2
134
0
Order By: Relevance
“…However, splicing sites cannot be assigned merely on the basis of splicing site scores, because we do not really know how the cellular splicing machinery is regulated during the selection of splicing sites (26). Furthermore, splicing during a viral infection is modulated by viral proteins, such as NS1 (27,54). Therefore, further studies are needed to confirm whether other novel viral proteins, some of which might not be functional, are expressed from these deduced spliced mRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, splicing sites cannot be assigned merely on the basis of splicing site scores, because we do not really know how the cellular splicing machinery is regulated during the selection of splicing sites (26). Furthermore, splicing during a viral infection is modulated by viral proteins, such as NS1 (27,54). Therefore, further studies are needed to confirm whether other novel viral proteins, some of which might not be functional, are expressed from these deduced spliced mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, all immature mRNAs always have the potential to be edited by splicing. Yet only the M and NS segments are known to encode viral proteins in spliced mRNAs (27). In the present study, we focused on the PB2 segment, which is one of the longest segments of influenza A virus, to explore whether a novel spliced mRNA from the PB2 segment encodes a novel viral protein.…”
mentioning
confidence: 99%
“…Multiple viruses regulate the cell splicing machinery to generate alternative viral RNA products. Several RNA viruses (35)(36)(37)(38) and DNA viruses (39) use extensive alternative splicing of their mRNAs. The influenza A virus NS1 protein disorganizes nuclear speckles and Cajal bodies and binds members of the snRNP family of splicing factors and proteins required for 3=-terminal polyadenylation of host transcripts to facilitate splicing of viral RNAs (35).…”
Section: Discussionmentioning
confidence: 99%
“…Each ssRNA segment encodes at least one protein. 6 For almost three decades after the genome of influenza A viruses was first mapped, the genome of influenza A viruses was thought to encode 10 proteins. However, new findings have revealed that this eight-segment genome could encode up to 18 proteins, and more proteins could be discovered in the future.…”
Section: Introductionmentioning
confidence: 99%